Diagnóstico de sífilis e outras possíveis infecções sexualmente transmissíveis em portadores do HIV/AIDS na região de tríplice fronteira internacional Brasil-Paraguai-Argentina - Benitez, Fabio João (2022)
Introduction: The spread of HIV, Syphilis and other Sexually Transmitted Infections (STI) in border areas is a reality conditioned by several factors, especially when the HIV carrier does not use condoms during sexual intercourse. Objective: To detect Syphilis and other STI diagnoses and also risky sexual behavior in HIV/AIDS patients in a triple international border region. Materials and Methods: HIV/AIDS patients treated at the Specialized Assistance Service in the city of Foz do Iguaçu - Paraná, Brazil, were evaluated using a structured form containing 16 objective questions addressing sociodemographic and epidemiological characteristics, situations of risk and sexual behavior with a fixed and/or occasional partner, and by information systems (notification of conditions and laboratory tests) to obtain the diagnosis of Syphilis, other STI and HIV Viral Load. The association between the infected state and the independent variables was evaluated using Fisher's Exact Test, and the variables that presented p≤0,05 were included in the multivariate analysis Odds Ratio, confidence interval of 95,0% (p≤0,05). Results: Of the 307 HIV/AIDS carriers evaluated, the prevalence of Syphilis was 9,5% and of other STI was 5,2%. Among the Syphilis diagnoses, the prevalence of age was between 18 and 44 years old (96,6%), 96,6% with Brazilian nationality, 93,1% residents in Foz do Iguaçu, 20,7% undergraduate student in Ciudad del Este, 65,5% with 12 years of schooling or more, 69,0% single/not in a relationship, 79,3% homosexuals, 93,0% male gender identity, 82,8% had no female sexual partner in the last 12 months, 55,2% had from 1 to 5 male sexual partners in the last 12 months, 27,6% used condoms less than half of the times and 96,6% had already received guidance on the prevention of HIV and other STI (p<0,05). As for the diagnoses of other STI, 75,0% reported having a monthly income of up to 2 minimum wages and 75,0% had from 1 to 5 male sexual partners in the last 12 months (p<0,05). The frequency of HIV Viral Load Testing was 25,7% in the last 12 months and 12,1% had detected Viral Load (from 1 to 823.829 copies/mL) in the last test performed. Conclusion: The diagnosis of Syphilis and other STI resulted from risky sexual behavior among HIV infected people, which contributes to the increase of HIV/AIDS in the Brazil-Paraguay-Argentina triple international border region.